Manajemen Pembelajaran pada Masa Pandemi Covid-19 di Madrasah Aliyah - Fatkurrozi Fatkurrozi; Hamengkubuwono Hamengkubuwono; Kusen Kusen (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The research objectives are for learning planning in the Covid-19 pandemic, implementing Covid-19 pandemic learning, and evaluating learning for the Covid-19 pandemic at Madrasah Aliyah Riyadus Sholihin. The research method uses qualitative methods. Data collection techniques through interviews, observation, and documentation. The data analysis technique is through the data collection process, namely data reduction, data presentation, and data inference. The results of the study show that teachers carry out learning planning for the Covid-19 pandemic, namely planning based on the existing curriculum with the development of lesson plans. Furthermore, the determination of WhatsApp Groups (implemented by the homeroom teacher) as a learning tool and YouTube as a learning medium, reduces learning hours while managers and supervisors are carried out by admins. Evaluation of learning during the Covid-19 pandemic showed the ineffectiveness of learning which was marked by obstacles in the form of internet network constraints, decreased student enthusiasm, students did not focus on learning, difficulty to understand, students did not actively participate in learning, students collected assignments, the fatigue of the students in learning the Covid-19 pandemic and the homeroom teacher. In conclusion, the learning management of the Covid-19 pandemic is in the form of, a) educational planning with learning policies, namely education of planning, which means education planning for one time use; b) Madrasah Aliyah Riyadus Sholihin Musi Rawas does not carry out supporting activities and supporting learning activities, as well as work plans and their elaboration in the process; c) there is no definite evaluation pattern and meetings are held in learning management planning during the covid-19 pandemic. Keywords: Learning Management, Covid-19 Pandemic